Developing a Performance-Based Assessment to Measure Pre-Service Secondary Teachers’ Digital Competence to Use Digital Mathematics Tools - Seifert, Hannes; Lindmeier, Anke (Journal für Mathematik-Didaktik, 2024)
Digital competence is an increasingly important component of teacher competence. So far, self-reports are a commonly used, efficient, but potentially problematic assessment method. Standardized and valid assessments to measure digital competence for teachers—particularly of a concrete subject—and proximally to performance are lacking. To address this, we developed a performance-based assessment for pre-service mathematics teachers based on the TPACK and DigCompEdu frameworks, both widely used in teacher education. The test focuses on digital competence related to mathematics tools such as computer algebra systems, dynamic geometry, and spreadsheet software, where technical-mathematical and pedagogical competences are required. This report presents the assessment design and provides validity evidence regarding the internal structure of the test, its sensitivity to intervention, and the relation of the scores to external variables, like affective-motivational aspects or prior experiences with tools based on a study with N = 118 pre-service teachers. First, we confirmed a two-dimensional structure of technical-mathematical and pedagogical aspects of digital competence through a confirmatory factor analysis. Second, expectations regarding the relation to external variables were partially confirmed. Third, we identified the sensitivity of the assessment to an intervention. Especially as expected, the relations between scores and self-assessment results were mixed. Our results indicate that the assessment is suitable for measuring pre-service mathematics teachers’ digital competence in two aspects close to performance. We discuss possible uses to evaluate learning opportunities in teacher education.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Competence Measurement; Digital Competence; Digital Mathematics Tools; Performance Assessment; Pre-Service Teachers; TPACK